Coffee By-Products as Sustainable Novel Foods: Report of the 2nd International Electronic Conference on Foods—“Future Foods and Food Technologies for a Sustainable World” - Dirk W. Lachenmeier; Steffen Schwarz; Jörg Rieke-Zapp; Ennio Cantergiani; Harshadrai Rawel; María Angeles Martín-Cabrejas; Maria Martuscelli; Vera Gottstein; Simone Angeloni (Foods, 2021)
The coffee plant Coffea spp. offers much more than the well-known drink made from the roasted coffee bean. During its cultivation and production, a wide variety of by-products are accrued, most of which are currently unused, thermally recycled, or used as fertilizer or animal feed. Modern, ecologically oriented society attaches great importance to sustainability and waste reduction, so it makes sense to not dispose of the by-products of coffee production but to bring them into the value chain, most prominently as foods for human nutrition. There is certainly huge potential for all of these products, especially on markets not currently accessible due to restrictions, such as the novel food regulation in the European Union. The by-products could help mitigate the socioeconomic burden of coffee farmers caused by globally low coffee prices and increasing challenges due to climate change. The purpose of the conference session summarized in this article was to bring together international experts on coffee by-products and share the current scientific knowledge on all plant parts, including leaf, cherry, parchment and silverskin, covering aspects from food chemistry and technology, nutrition, but also food safety and toxicology. The topic raised a huge interest from the audience and this article also contains a Q&A section with more than 20 answered questions.